Fiber Misalignment Effect On Compressive Properties Of Jute And Kevlar Composite Under Impact And Static Loading - Lim, Kwan Hue (Universiti Sains Malaysia, 2022)
These days, composite materials are frequently used. Due to its low cost, great strength, and light weight, it has a wide range of uses. However, fiber misalignment problem always inevitable during manufacture and might affects fiber its compressive strength. Weaved fibres aim to address the issue of the extremely anisotropic behaviour of unidirectional composites. Therefore, this research is to investigate the fiber misalignment effect on compressive properties of jute and kevlar composite under impact loading with 1.0 bar, 1.25 bar and 1.5 bar using split hopkinson pressure bar (SHPB). Besides, static loading testing is done using ultimate tensile machine (UTM) with about 0.08mm/s to study its compressive properties. The support of using scanning electron microscope (SEM), high speed camera (HSC) and camera phone is to figure the failure mechanism of jute and kevlar specimen under dissimilar parameters. The results demonstrate the failure stress and strain of the jute composite fall by 10.1% and 2.11%, respectively, as impact loading. Under static loading, the failure stress and strain are successively lowered by 12.5% and 19.5%. In all different pressure bars of impact testing, the kevlar composite shows an increase in failure stress of 129.1% from 0° to 4° and a notable increase in failure strain of 533.3%. The failure stress and failure strain of kevlar composite increased significantly by 252.4% but dropping by 3.9% under static loading.